Growth and fatty acid profiles of Halophytophthora vesicula and Salispina spinosa from Philippine mangrove leaves. (1st September 2019) - Caguimbal, N.A.L.E.; Devanadera, M.K.P.; Bennett, R.M.; Arafiles, K.H.V.; Watanabe, K.; Aki, T.; Dedeles, G.R.
Abstract: Studies on marine‐sourced fatty acids have gathered significant interest recently as an important component of aquaculture feeds and of biofuel production. Of the organisms capable of producing fatty acids, marine oomycetes are promising model organisms. One group of marine oomycetes are the Halophytophthora spp. which is known to have an important role in leaf decomposition, thereby changing the plant debris into exudates which are usable to consumers in the mangrove ecosystems. This study reports the three mangrove oomycetes isolated from Philippine mangrove forests, identified herein as Halophytophthora vesicula AK1YB2 (Aklan), H. vesicula PQ1YB3 (Quezon) and Salispina spinosa ST1YB3 (Davao del Norte). These isolates were subjected to growth analyses using varying incubation parameters (salinity level and pH), and for fatty acid production. Results revealed the presence of different fatty acids such as Arachidonic acid, Linoleic acid and Vaccenic acid when grown on V8S and PYGS media. This study is the first observation of fatty acids from S. spinosa and H. vesicula from the Philippines. Significance and Impact of the Study: Tropical Philippines straddling west of the Pacific Ocean and East of South China Sea is rich in marine and estuarine oomycetes. These micro‐organisms, hitherto poorly known and unstudied in the country, play an important role in the nutritive cycle of the mangrove ecosystem. Due to the increasing demand for an alternative source of fatty acids, species of Oomycetes isolated from select mangrove forests in Luzon, Visayas and Mindanao were analysed for their fatty acid contents. Prospects for industrially‐important fatty acids make these Oomycetes all‐important to study in applied microbiology in the Philippine setting where these structurally simple micro‐organisms abound.